The Development of Mathematical Modelling Representing Tuning Slot Parameters Versus Resonant Frequency - Mohamad, Farahatul Khalida (Universiti Teknologi PETRONAS, 2014)
To design a Dielectric Resonator Antenna (DRA) with desired resonant frequency, Heuristic method must be used. Thus, it consume a lot of time, effort and cost. It is because, currently there are no specific mathematical model to determine the resonant frequency. Eventhough, the resonant frequency can be obtained through simulation, but it will consume a lot of time an effort. Hence, this project is carried out to develop mathematical model which represent tuning slot parameters of DRA versus resonant frequency. The tuning slot parameters varied in this project is C-slot position from input port of antenna. The position of the slot from the input port of the antenna have been varied and resonant frequency at each position is determined. A series of preliminary simulation and design have been performed by utilizing CST Microwave Studio Software. From the simulations, the relationship between the C-slot position and resonant frequency is studied and a mathematical model is developed.